Early Risk Factors for Retinopathy of Prematurity in Very and Extremely Preterm Chinese Neonates - Huang, Hai-Bo; Chen, Yi-Hua; Wu, Jing; Hicks, Matt; Yi, Yan-Zhi; Zhang, Qian-Shen; Chow, Chun-Bong; Cheung, Po-Yin (Frontiers in Pediatrics, 2020)
Objective: To investigate the incidence and risk factors of retinopathy of prematurity (ROP) in very and extremely preterm (28+0- <32+0, and <28+0 weeks gestation, respectively) neonates, and the predictive factors for ROP in the early hours after birth and during hospitalization. Methods: Using a prospective database supplemented with a retrospective chart review, we identified preterm neonates born at gestation <32 weeks at the University of Hong Kong-Shenzhen Hospital between January 2015 and August 2018. Demographic and clinical variables were studied including indicators of disease acuity in the first 24 h after birth. We also compared the difference in risk factors between survivors with ROP and survivors without ROP. Results: During the study period, there were 529 preterm neonates admitted to our neonatal intensive care unit with 120 (23%) born at <32 weeks' gestation. Thirteen (11%) neonates died. Among the 107 survivors, 23 (21%) had ROP, of whom five (22%) received laser and/or medical therapy for severe ROP. Compared with survivors without ROP, infants with ROP had lower mean blood pressure in the first 12 and 24 h after birth, respectively. Using multivariate regression, gestation age, mean blood pressure in the first 12 h after birth, hospital length of stay, and total days of blood gases pH <7.2 were independent risk factors for ROP. Conclusions: In this small cohort of Chinese neonates born <32+0 weeks' gestation, survivors with ROP had a lower blood pressure in the early hours after birth, younger gestation, longer hospital stay, and duration of acidosis when compared to those without ROP.